Characterizing Esophageal Motility in Neonatal Intensive Care Unit Patients Using High Resolution Manometry - Rayyan, Maissa; Omari, Taher; Cossey, Veerle; Allegaert, Karel; Rommel, Nathalie (Frontiers in Pediatrics, 2022)
Objective To characterize esophageal motility and esophago-gastric junction (EGJ) function during feeding in neonatal intensive care unit (NICU) patients. Patients and Methods High resolution manometry with impedance (HRIM) was used to investigate esophageal motility and EGJ function in patients admitted to the NICU. Twenty-eight preterm born infants with bronchopulmonary dysplasia (BPD), 12 born with isolated congenital diaphragmatic hernia (iCDH), and 10 with esophageal atresia (EA) were included. Thirteen healthy infants were included as controls. Esophageal motility and EGJ function were analyzed using objective esophageal bolus transport parameters. Results Normal esophageal peristaltic wave patterns were observed in all investigated infants without EA. Nine of 10 patients with EA presented with abnormal esophageal motor wave patterns. A total of 224 nutritive swallows were analyzed (controls, n = 48; BPD, n = 96; iCDH, n = 60; EA, n = 20). Infants with BPD and iCDH had similar distal contractile strength (DCI) compared to healthy controls, while in patients with EA, DCI was significantly lower (Kruskal-Wallis test, p=0.001). In most infants, EGJ relaxation after swallowing was unaffected. EGJ barrier function, in terms of EGJ-contractile integral, also appeared well-developed and did not differ significantly among patient groups. Conclusions We conclude that esophageal motility studies using pressure-impedance analysis are feasible in young infants. Bolus transport mechanisms following nutritive swallows appeared well-established in all investigated infants with the exception of those with EA. EGJ relaxation was also functional after deglutition and EGJ function as an anti-reflux barrier appeared well-developed in all investigated NICU groups.